Problematika Penerapan Pendaftaran Izin Berusaha Berbasis Rencana Detail Tata Ruang Dalam Sistem Pertanahan Nasional - I Gusti Ayu Manik Silvia Dewi; Putu Eka Trisna Dewi (Lembaga Penelitian Pengabdian Masyarakat dan Pusat Kajian - Universitas Ngurah Rai, 2026)
The implementation of risk-based business licensing through the Online Single Submission (OSS) system places the Detailed Spatial Plan (RDTR) as a key basis for issuing business permits. This policy aims to accelerate licensing procedures and enhance legal certainty. However, in practice, RDTR-based business licensing raises juridical issues within the national land law system. This study examines the juridical problems of RDTR-based business licensing and their implications for legal certainty. Using normative legal research with statutory and conceptual approaches, the study finds inconsistencies between the spatial planning and land law regimes, weak examination of land rights legality, and potential violations of good governance principles. Additionally, the uneven availability of RDTR across regions leads to unequal legal treatment. Therefore, strengthening the integration of spatial planning and land administration is essential to ensure legal certainty in business licensing.